2013
DOI: 10.1007/978-3-642-41335-3_29
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Scholarly Data with Rexplore

Abstract: Abstract. Despite the large number and variety of tools and services available today for exploring scholarly data, current support is still very limited in the context of sensemaking tasks, which go beyond standard search and ranking of authors and publications, and focus instead on i) understanding the dynamics of research areas, ii) relating authors 'semantically' (e.g., in terms of common interests or shared academic trajectories), or iii) performing fine-grained academic expert search along multiple dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 17 publications
0
108
0
Order By: Relevance
“…This indicates that two topics can be treated as equivalent for the purpose of exploring research data -e.g., "ontology mapping" and "ontology matching". Skos:broaderGeneric and relatedEquivalent are necessary to build a taxonomy of topics and to handle different labels for the same research areas, while contributesTo provides an additional relationship that can be used to assist the user in browsing research topics [5] and analyzing research data -e.g., for identifying topic-based research communities [10].…”
Section: Data Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This indicates that two topics can be treated as equivalent for the purpose of exploring research data -e.g., "ontology mapping" and "ontology matching". Skos:broaderGeneric and relatedEquivalent are necessary to build a taxonomy of topics and to handle different labels for the same research areas, while contributesTo provides an additional relationship that can be used to assist the user in browsing research topics [5] and analyzing research data -e.g., for identifying topic-based research communities [10].…”
Section: Data Modelmentioning
confidence: 99%
“…The output is a populated OWL ontology describing the semantic relationships between the research topics identified from the set of keywords and the other data provided as input. This semantic network can then be used for improving the processes of searching and performing analytics on scholarly data [3,5,6,7]. As in the case of the Klink algorithm, Klink-2 generates an ontology of research topics linked by the three relationships introduced above.…”
Section: Overview Of Klink-2mentioning
confidence: 99%
See 3 more Smart Citations